Employee Empowerment in the Decision-Making Process: Evidence from the Food and Beverage Industry in Indonesia - Yit, Michelle; Bangun, Yuniros (Jurnal Manajemen Teknologi, 2020)
Abstract. A study was conducted to investigate the employee empowerment in decision-making process in food and beverage (F&B) industry in Indonesia. The rise of educated middle class population and increase of consumer trends has compelled the F&B manufactures to make new innovations. The employment situation showed that organizations have difficulty retaining talents. Employee empowerment is closely related to decision making where the superior shares authority with the employee. A conceptual model was built where the leader, employee, leader and employee relation and organizational tools profiles were measured on employees' level of involvement on types of decisions in a food and beverage factory. Nine decision making questions common in food factories were selected and validated. A quantitative survey was conducted with 203 respondents'. Using multiple regression analysis, the overall model of each leader, employee, leader and employee relation, and organizational tools proved significant and positively predicting decision making and innovation. In addition, seniority position and level also showed significance. F&B manufacturers should use employee empowerment as a key strategy to stay competitive, build an innovative culture,and retaintalented employees.Keywords: Employee empowerment, decision making, innovation, food industry, IndonesiaAbstrak. Studi dilakukan untuk meneliti pemberdayaan pegawai dalam pengambilan keputusan pada industi makanan dan minuman di Indonesia. Peningkatan populasi kelas menengah yang terdidik dan peningkatan tren konsumer telah mempercepat langkah manufaktur makanan dan minuman untuk berinovasi dalam produk baru. Situasi kekaryawanan di Indonesia menunjukkan kesulitan perusahaan dalam mempertahankan pegawai. Pemberdayaan karyawan berhubungan erat dengan pengambilan keputusan dimana pengusaha atau manajer membagi kekuasaan kepada karyawan. Model konspetual dibuatdimana profil pimpinan, profil karyawan, alat organisasi, hubungan karyawan dan pimpinan, diukur berdasarkan tingkat keterlibatan karyawan dalampengambilan keputusan. Sembilan keputusan terkait pabrik makanan dan minuman dipilih dan divalidasi. Survey kuantitatif dilakukan secara nasional terhadap 203 responden. Dari hasil analisa multiple regression, model keseluruhan pada karyawan, pimpinan, alat organisasi, serta hubungan pimpinan dan karyawan, terbukti valid. Posisi serta level dari pimpinan perusahaan ke responden juga mempengaruhi perberdayaan karyawan. Manufaktur makanan dan minuman direkomendasikan untuk menggunakan pemberdayaan karyawan sebagai strategi kunciuntuk tetap kompetitif, membangun budaya inovasi, dan mempertahankan karyawan bertalenta.Kata kunci: pemberdayaan karyawan, pengambilan keputusan, inovasi, makan dan minuman, Indonesia